2003
DOI: 10.1074/jbc.m210279200
|View full text |Cite
|
Sign up to set email alerts
|

Egr1 Promotes Growth and Survival of Prostate Cancer Cells

Abstract: In the majority of aggressive tumorigenic prostate cancer cells, the transcription factor Egr1 is overexpressed. We provide new insights of Egr1 involvement in proliferation and survival of TRAMP C2 prostate cancer cells by the identification of several new target genes controlling growth, cell cycle progression, and apoptosis such as cyclin D2, P19ink4d, and Fas. Egr1 regulation of these genes, identified by Affymetrix microarray, was confirmed by real-time PCR, immunoblot, and chromatin immunoprecipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 64 publications
7
128
0
Order By: Relevance
“…Another Affymetrix microarray analysis compared mouse prostate cancer cells TRAMP-C2 in the presence or absence of Egr1 antisense. 64 A total of 960 genes were regulated by endogenous Egr1 and several new targets were identified. Some of these play important roles in cell proliferation or apoptosis, such as cyclin D2, p19INK, Fas, and TGFb1.…”
Section: Egr1-induced Oncogenesis Of Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Another Affymetrix microarray analysis compared mouse prostate cancer cells TRAMP-C2 in the presence or absence of Egr1 antisense. 64 A total of 960 genes were regulated by endogenous Egr1 and several new targets were identified. Some of these play important roles in cell proliferation or apoptosis, such as cyclin D2, p19INK, Fas, and TGFb1.…”
Section: Egr1-induced Oncogenesis Of Prostate Cancermentioning
confidence: 99%
“…[73][74][75] An important feature of the suppressor network in prostate tumors is Egr1-induced TGFb1. 61,63,64 TGFb1 has diverse roles and may have the net effect of promoting the progression of prostate cancer (reviewed in Albrecht et al 72 and Zheng et al 73 ). TGFb1 may also facilitate detachment and metastasis.…”
Section: Egr1-induced Oncogenesis Of Prostate Cancermentioning
confidence: 99%
“…Egr1 is known to regulate the promoters of both the PTEN and p53/ TP53 tumor-suppressor genes (Yu et al, 2007) and was shown to physically interact with the p53 protein itself (Liu et al, 2001). Egr1 upregulates PTEN expression in response to both radiation and calyculin A (Virolle et al, 2001(Virolle et al, , 2003. In addition, Egr1-mediated control of p53 and PTEN was shown to have a role in DNA damage-induced apoptosis in both prostate and breast cancer cells (Adamson and Mercola, 2002;Adamson et al, 2003;Yu et al, 2007).…”
Section: Rps14: a Role For Defective Translation In Mds?mentioning
confidence: 99%
“…The induction of Egr-1 by external stimuli is generally transient but appears to be sustained in some prostate tumor cell lines and tumors, suggesting that Egr-1 stimulates tumor cell growth and that could have an important function because its expression level increases with the degree of malignancy as measured by the Gleason grade of the tumor (1). This seems to be specific to prostate tumor cells, because in mammary and lung tumors, as well as most normal tissues, Egr-1 expression is low (2)(3)(4)(5)(6). In addition Egr-1 overexpression is correlated with the loss of its co-repressor NAB2 in primary prostate carcinoma (6)(7)(8).…”
Section: Introductionmentioning
confidence: 98%
“…This disruption of the balance between Egr-1 and NAB2 expression results in a high Egr-1 transcriptional activity in prostate carcinoma cells (1). In contradiction, in breast, lung and brain tumors, Egr-1 expression is often absent or reduced and when re-expressed, results in growth suppression (2,(4)(5)(6)(7)(8)(9)(10). Another contradiction is that after stress stimuli to some cell types, Egr-1 is required for programmed cell death or apoptosis in both normal and tumor cells (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%